A Chebyshev Polynomial on Torque and Thrust Coefficients of Mathematical Propeller Properties for a LNG Manoeuvring Simulation - Priyanto, Agoes; Zamani, Mohd.; Izzudin, Nur; Sunarsih, Sunarsih (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
The estimated torque and thrust coefficients in four quadrants of marine propeller in a LNG manoeuvre control system is essential for the total performance of the vessel. A Chebyshev n-order polynomial that approximated a continuous function over the interval advance speed J [-1, 1] to calculate the torque and thrust coefficients as well as the shaft speed, is utilized to get the propeller properties. The Dynamical modeling and simulation of the marine propeller across the four quadrants are schemed and applied to the marine propeller B-4.58. The results are compared with both open water experiments and open water numerical tests using ANSYS-Fluent. The comparisons show that the chebyshev polynomial agreed well with both experiments and numerical tests and deduce that the polynomial provides a new practically approach estimation on torque and thrust coefficients in four quadrants of marine propeller for the vessel operations. Then the polynomial coefficients from Chebyshev n-order polynomial were used to express the mathematical model for the propeller thrust and torque characteristics and applied in the manoeuvring simulation programming.